Impact of PPh Article 23 Recognition and Tax Payable on Net Income: Publicly Manufacturing Firms - Widantia, Kemuning Ananta; Mishelelion, Mishelelion (SAN Scientific, 2025)
The purpose of this study is to determine whether the simultaneous effect of Income Tax Article 23 and tax payable on net profit, to determine whether the recognition of Income Tax Article 23 carried out by manufacturing firms affects the amount of net profit and determine whether the tax payable carried out by manufacturing firms affects the amount of net profit. This type of research is a quantitative research type. The type of data used in this study is secondary data in the form of financial statements of firms, such as the firm's profit and loss report and its Income Tax. The population in this study was all manufacturing firms listed in the firm report. The findings of Income Tax Article 23 affect net profit in manufacturing sector firms. Hypothesis 1 states that there is an influence between Income Tax Article 23 on Net Profit. It can be concluded that Hypothesis 2, which states that there is an influence between tax payable and net profit, is accepted. Important managerial implications for manufacturing firms, especially in optimizing tax planning to improve financial efficiency.